Valgus Osteotomy in Neglected Femoral Neck Fractures: A Case Report (Mugda Medical College Journal, 2025)
Femoral neck fracture continues to be regarded as an “unsolved fracture.” In developing countries, neglected neck of femur (NOF) fractures frequently lead to complications such as osteopenia, neck resorption, and avascular necrosis (AVN). Neglected femoral neck fractures in young patients present significant challenges due to complications such as nonunion and AVN. Preservation of the femoral head is paramount in managing these cases. Valgus intertrochanteric osteotomy, combined with dynamic hip screw (DHS) fixation, offers a biomechanical solution by converting shear forces into compressive forces, thereby promoting fracture healing. This case report details the management of a 16-year-old male with a neglected femoral neck fracture, successfully treated with valgus osteotomy and DHS fixation. The patient presented with a 2-year-old femoral neck fracture, classified as Garden IV, and exhibited symptoms of pain, restricted mobility, and limb shortening. Preoperative radiographs confirmed nonunion without signs of AVN. The surgical intervention involved valgus intertrochanteric osteotomy and fixation with a DHS, providing enhanced stability and compression. Postoperative care included physiotherapy focusing on gradual weight-bearing. This case highlights the efficacy of valgus intertrochanteric osteotomy with DHS fixation in treating neglected femoral neck fractures in young patients. The procedure is cost-effective, promotes fracture union, and preserves hip function with minimal complications. Given these outcomes, valgus osteotomy should be considered a primary treatment option for femoral neck nonunion in physiologically young individuals.Mugda Med Coll J. 2025; 8(1): 72-75